The Heart of the Alzheimer's: A Mindful View of Heart Disease - Evangelisti, Alessandro; Butler, Helen; del Monte, Federica (Frontiers in Physiology, 2021)
Purpose of Review This review summarizes the current evidence for the involvement of proteotoxicity and protein quality control systems defects in diseases of the central nervous and cardiovascular systems. Specifically, it presents the commonalities between the pathophysiology of protein misfolding diseases in the heart and the brain. Recent Findings The involvement of protein homeostasis dysfunction has been for long time investigated and accepted as one of the leading pathophysiological causes of neurodegenerative diseases. In cardiovascular diseases instead the mechanistic focus had been on the primary role of Ca2+ dishomeostasis, myofilament dysfunction as well as extracellular fibrosis, whereas no attention was given to misfolding of proteins as a pathogenetic mechanism. Instead, in the recent years, several contributions have shown protein aggregates in failing hearts similar to the ones found in the brain and increasing evidence have highlighted the crucial importance that proteotoxicity exerts via pre-amyloidogenic species in cardiovascular diseases as well as the prominent role of the cellular response to misfolded protein accumulation. As a result, proteotoxicity, unfolding protein response (UPR) and ubiquitin-proteasome system (UPS) have recently been investigated as potential key pathogenic pathways and therapeutic targets for heart disease. Summary Overall, the current knowledge summarized in this review describes how the misfolding process in the brain parallels in the heart. Understanding the folding and unfolding mechanisms involved early through studies in the heart will provide new knowledge for neurodegenerative proteinopathies and may prepare the stage for targeted and personalized interventions.